Effect Of NAA And Kinetin Administration On Callus Induction In Vanilla Plant Stem Explants (Vanilla planifolia Andrews) - Dhavin, Muhammad; Nurokhman, Amin; Arif Yachya; Ummi Hiras Habisukan; Yustina Hapida; Anggun Wicaksono; Weni Lestari (Universitas PGRI Adi Buana Surabaya, 2025)
Vanilla (Vanilla planifolia Andrews) is a plantation plant that is used for its fruit. Indonesia is one of the countries that exports vanilla and has climate factors that support increasing vanilla production to meet global demand, One of the efforts that can be made in vanilla propagation is through plant tissue culture. This research aims to induce calluses. This study used a Random Design using stem explants and several different hormone concentrations, namely: 0.0 ppm NAA and 0.0 ppm Kinetin, 1.0 ppm NAA and 0.5 ppm Kinetin, 1.0 ppm NAA and 1.0 ppm Kinetin, 2.0 ppm NAA and 0.5 ppm Kinetin, 2.0 ppm NAA and 1.0 ppm Kinetin, 2.0 ppm NAA and 2.0 ppm Kinetin. There was an effect on the administration of NAA and Kinetin on callus induction in the explants of the vanilla plant (Vanilla planifolia Andrews). It is based on the Anova one-way Hypothesis Test with a significance value of 0.000 (Asymp. Sig <0.05) then Ho was rejected and H1 was accepted. The optimal concentration to induce callus in stem explants is the administration of 1.0 ppm NAA + 0.5 ppm Kinetin with an average callus growth rate of 7 HST and a 100% callus growth percentage of explants. Keywords: Vanilla, induction, callus, tissue culture, hormones